The role of BRAF mutations in primary melanoma growth rate and survival. (13th June 2015) - Mar, V.J.; Liu, W.; Devitt, B.; Wong, S.Q.; Dobrovic, A.; McArthur, G.A.; Wolfe, R.; Kelly, J.W.
Summary Background The clinical behaviour and prognosis of primary melanomas harbouring BRAF mutations is not fully understood. Objectives To investigate the effect of mutation status on primary melanoma growth rate and melanoma‐specific survival (MSS). Methods A prospective cohort of 196 patients with stage I–III primary cutaneous melanoma were followed for a median of 92 months, pre‐dating the institution of BRAF inhibitor therapy. Clinicopathological variables were correlated with mutation status and hazard ratios (HRs) estimated for MSS. Results Of 196 tumours, 77 (39·2%) were BRAF V600E, 10 (5·1%) BRAF V600K and 33 (16·8%) were NRAS mutant. BRAF V600E mutant melanomas were associated with favourable clinical characteristics and tended to be slower growing compared with BRAF V600K, NRAS mutant or BRAF/NRAS wild‐type tumours (0·12 mm per month, 0·61 mm per month, 0·36 mm per month and 0·23 mm per month, respectively; P = 0·05). There were 39 melanoma deaths, and BRAF mutant melanomas were associated with poorer MSS in stage I–III disease [HR 2·60, 95% confidence interval (CI) 1·20–5·63; P = 0·02] and stage I–II disease (HR 3·39, 95% CI 1·12–10·22; P = 0·03) after adjusting for other prognostic variables. Considered separately, BRAF V600E mutant melanomas were strongly associated with MSS independently of thickness and nodal status (HR 3·89, 95% CI 1·67–9·09; P < 0·01) but BRAF V600K mutant tumours were not (HR 1·19, 95% CI 0·36–3·92; P = 0·77). Conclusions The presence of a BRAF mutation does not necessarily 'drive' more rapid tumour growth but is associated with poorer MSS in patients with early‐stage disease.